Antioxidant and radical scavenging properties of Carthamus caeruleus L extracts grow wild in Algeria flora - Baghiani, Abderrahmane; Boumerfeg, Sabah; Belkhiri, Farida; Khennouf, Seddik; Charef, Noureddine; Harzallah, Daoud; Arrar, Lekhmici; Abdel-Wahhab, Mosaad Attia (Comunicata Scientiae, 2010)
Four sub-fractions of Carthamus caeruleus L (which belongs to the family Asteraceae) root extracts, i.e., methanol (CE), chloroform (CHE), ethyl acetate (EAE) and aqueous (AE) extracts were screened for their total phenolics, flavonoids and possible antioxidant activities, using DPPH free radical-scavenging and β-carotene/linoleic acid assays. The results indicated that total polyphenols were highest in EAE followed by CHE. However, the free radical scavenging activity of CHE was higher than the other extracts with an IC50 value of 53.26 µg/mL. Determination of quercetin, gallic acid and rutin showed antioxidant activity as positive controls in parallel experiments. Moreover, oxidation of linoleic acid was effectively inhibited by AE, EAE and CE which were too close to each other. Also, the CHE was more effective compared to the synthetic antioxidant BHT. It could be concluded that Carthamus caeruleus L growing wild in the Mediterranean regions and especially in Algeria has a potent antioxidant activity and could be evaluated as a starting point for further investigations.